Laks, A.; Most, G. (2016). Early Greek Philosophy (9 vols.). Cambridge MA, Loeb Classical Library; Laks, A., Most, G. (2016). Les débuts de la Philosophie, des premiers penseurs grecs Ã Socrate. Paris, Fayard. - Rossetti, Livio (Revista Archai, 2017)
Laks, A.; Most, G. (2016). Early Greek Philosophy (9 vols.). Cambridge MA, Loeb Classical Library; Laks, A., Most, G. (2016). Les débuts de la Philosophie, des premiers penseurs grecs Ã Socrate. Paris, Fayard.